Effect of Different Source of Nutrients on the Performance, Growth and Quality of Summer Onion (Journal of Environmental Science and Natural Resources, 2015)
The field experiments were conducted for one season rabi 2008-09 at the Multilocation testing site Magura on calcareous soil to study the effect of integrated nutrient management on the growth and yield of onion (cv. BARI piaj 2). The experiment was laid out in a RCB design. There were five treatments involving four inorganic levels and organic levels another absolute control (no manure and no NPK). Higher level of inorganic T1 i.e., (120-45-85-40 kg ha-1 NPK S+ 5 t/ha CD) produced significantly higher bulb yield (18.76 t/ha) which was on par with T4 (17.87 t/ha) i.e., 5 t/ha poultry manure + remaining amount from inorganic fertilizer T2. The results also indicated that the same treatments recorded the highest single bulb weight, bulb yield as well as gross returns and MBCR (7.14) as compared to other treatments.DOI: http://dx.doi.org/10.3329/jesnr.v6i1.22059 J. Environ. Sci. & Natural Resources, 6(1): 159-162 2013